Evaluation of Antidiabetic and Antioxidant Activity of Leaf Extract and Solvent Fractions of Hypoestes forskaolii (Val) (Acanthaceae) in Mice - Wakene W; Asmamaw S; Kahaliw W (Dove Medical Press, 2021)
Wakuma Wakene,1 Solomon Asmamaw,2 Wubayehu Kahaliw2 1Department of Pharmacy, College of Health Sciences, Mettu University, Mettu, Ethiopia; 2Department of Pharmacology, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, EthiopiaCorrespondence: Wakuma Wakene Tel +251 963421238Email wakewakish05@gmail.comBackground: Currently, there is a demand for new antidiabetic drugs from natural therapeutic agents, and diabetes mellitus disease is global epidemic. The leaf of Hypoestes forskaolii has been used in the traditional health system for the management of diabetes mellitus in Ethiopia and Eritrea. The aim of this study was to evaluate in vivo antidiabetic, antihyperlipidemic and in vitro antioxidant activity of leaf extract and solvent fractions of the leaf of H. forskaolii (Vahl) in mice.Methods: The blood glucose-lowering activities of leaf extract and solvent fractions of the leaf of H. forskaolii were screened in the normoglycemic, glucose loaded, and streptozotocin-induced diabetic mice models. In the treatment of streptozotocin-induced diabetic mice with leaf extract and solvent fractions, weight and lipid profile was measured. Antioxidant activity of the plant leaf extract was determined using DPPH assay.Results: The leaf extract of H. forskaolii showed significant blood glucose reduction in the normoglycemic model and glucose loaded test at doses of 200 mg/kg (34.1%, p < 0.001 and 55.5%, p < 0.001), respectively, as compared to the normal control. In the streptozotocin-induced diabetic model, extract and solvent fractions significantly (p < 0.001) reduced blood glucose level at all tested doses (100mg/kg, 200mg/kg and 400mg/kg) on the 14th day as compared to diabetic control. In addition, a significant reduction (p < 0.001) of serum TC, VLDL, LDL, TG was observed. In the antioxidant activity test, the IC50 values of extract and a standard drug (ascorbic acid) were 4.87μg/mL and 15.7μg/mL, respectively.Conclusion: The present study showed that the methanolic leaf extract and solvent fractions of H. forskaolii have antidiabetic, and antioxidant activity that provides a scientific support for the local use of the plant leaves in the treatment of diabetes.Keywords: diabetic mellitus, H. forskaolii, streptozotocin, hyperlipidemia